MYBA From Blueberry (Vaccinium Section Cyanococcus) Is a Subgroup 6 Type R2R3MYB Transcription Factor That Activates Anthocyanin Production - Plunkett, Blue J.; Espley, Richard V.; Dare, Andrew P.; Warren, Ben A. W.; Grierson, Ella R. P.; Cordiner, Sarah; Turner, Janice L.; Allan, Andrew C.; Albert, Nick W.; Davies, Kevin M.; Schwinn, Kathy E. (Frontiers in Plant Science, 2018)
The Vaccinium genus in the family Ericaceae comprises many species, including the fruit-bearing blueberry, bilberry, cranberry, huckleberry and lingonberry. Commercially, the most important are the blueberries (Vaccinium section Cyanococcus), such as V. corymbosum (northern highbush blueberry), V. virgatum (rabbiteye blueberry) and V. angustifolium (lowbush blueberry). The rising popularity of blueberries can partly be attributed to their ‘superfood’ status, with an increasing body of evidence around human health benefits resulting from the fruit metabolites, particularly products of the phenylpropanoid pathway such as anthocyanins. Activation of anthocyanin production by R2R3-MYB transcription factors (TFs) has been characterized in many species, but despite recent studies on blueberry, cranberry and bilberry, no MYB anthocyanin regulators have been reported for Vaccinium. Indeed there has been conjecture that at least in bilberry, MYB TFs divergent to the usual type are involved. We report identification of MYBA from blueberry, and show through sequence analysis and functional studies that it is homologous to known anthocyanin-promoting R2R3-MYBs of subgroup 6 of the MYB superfamily. In transient assays, MYBA complemented an anthocyanin MYB mutant of Antirrhinum majus and, together with a heterologous bHLH anthocyanin regulator, activated anthocyanin production in Nicotiana benthamiana. Furthermore anthocyanin accumulation and anthocyanin structural gene expression (assayed by qPCR and RNA-seq analyses) correlated with MYBA expression: and MYBA was able to transactivate the DFR promoter from blueberry and other species. The RNA-seq data also revealed a range of other candidate genes involved in the regulation of anthocyanin production in blueberry fruit. The identification of MYBA will help to resolve the regulatory mechanism for anthocyanin pigmentation in the Vaccinium genus. The sequence information should also prove useful in developing tools for the accelerated breeding of new Vaccinium cultivars.